2021
DOI: 10.1021/acs.biomac.0c01562
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Ferritin Self-Assembly by Laser Light Scattering: Impact of Subunit Concentration, pH, and Ionic Strength

Abstract: Ferritins, the cellular iron repositories, are self-assembled, hollow spherical nanocage proteins composed of 24 subunits. The self-assembly process in ferritin generates the electrostatic gradient to rapidly sequester Fe­(II) ions, thereby minimizing its toxicity (Fenton reaction). Although the factors that drive self-assembly and control its kinetics are little investigated, its inherent reversibility has been utilized for cellular imaging and targeted drug delivery. The current work tracks the kinetics of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 57 publications
(164 reference statements)
0
45
0
Order By: Relevance
“…20 One study revealed that ferritin disassembles at an extremely acidic pH 1.5 and then shows a rapid reassembly upon return to neutral pH 7.0, accompanied by folding, followed by a slow phase in which the final 24-mer nanocage is formed. 20 Importantly, this fundamental work led to the rational redesign For each structure, the pentameric and hexameric units are shown in light and saturated colors, respectively. Within the expanded pentameric or hexameric units, the tryptophan (W) residues belonging to individual subunits are highlighted in red: Tm: W19, W48, W70, W90, and W180; Mx: W17, W96, and W155; and Qt: W95 and W154.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 One study revealed that ferritin disassembles at an extremely acidic pH 1.5 and then shows a rapid reassembly upon return to neutral pH 7.0, accompanied by folding, followed by a slow phase in which the final 24-mer nanocage is formed. 20 Importantly, this fundamental work led to the rational redesign For each structure, the pentameric and hexameric units are shown in light and saturated colors, respectively. Within the expanded pentameric or hexameric units, the tryptophan (W) residues belonging to individual subunits are highlighted in red: Tm: W19, W48, W70, W90, and W180; Mx: W17, W96, and W155; and Qt: W95 and W154.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moderate concentrations of sodium chloride ranging from 0.5 to 1.0 M notably enhanced rhFTL recovery and did not significantly attenuate the removal of impurities at pH 4.4. Recent research also revealed that ionic strength can facilitate ferritin self-assembly in vitro [29,30]. Perhaps this benefit mainly ascribes to the formation of a salt-bridge, which was reported to critically contribute to the physical stability of FTL [28].…”
Section: Discussionmentioning
confidence: 99%
“…38 Additionally, ferritin has been found to have a biphasic reassembly, where an initial fast step occurs with folding of subunits and unknown stable intermediates, followed by the slower restructuring of intermediates into the nanocage. 23 Data of pH 13 reassembly rate for Mx-Enc and Qt-Enc was not included, as the presence of aggregation prevented extraction of accurate DLS size values. This suggests that reassembly from the pH 13 disassembled state for the larger and more complex Mx-Enc and Qt-Enc may be prone to protein misfolding pathways and/or partial assembly, and thus, without additional re-engineering, may not be ideal for use in future applications.…”
Section: Supplementary Table S5 and S6) The Faster Reassembly After Ph 13 Disassembly Compared Tomentioning
confidence: 99%
“…For instance, the disassembly/reassembly of protein nanocages belonging to the ferritin family have been studied via a combination of: intrinsic tryptophan fluorescence (ITF), circular dichroism (CD), UV/VIS spectroscopy and synchrotron small-angle X-ray scattering (SAXS) measurements to assess protein conformation [19][20][21][22] , transmission electron microscopy (TEM) and dynamic light scattering (DLS) to evaluate structural integrity, shape and size distribution, and laser light scattering to monitor assembly kinetics. 23 One study revealed that ferritin disassembles at extremely acidic pH 1.5, then shows a rapid reassembly upon return to neutral pH 7.0, accompanied by folding, followed by a slow phase in which the final 24-mer nanocage is formed. 23 Importantly, this fundamental work led to the rational re-design of ferritin subunit interfaces, resulting in engineered nanocages capable of disassembly at a more amenable pH 4.0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation